Influence of oxygen on the interfacial bonding and mechanical properties in the particulate-reinforced aluminum matrix composites - Miran Joo; Donghyun Bae (Journal of Materials Research and Technology)
The reinforcing effect of nanoparticles in aluminum matrix nanocomposites (AMCs) is often underestimated, primarily due to weak mechanical bonding at the nanoparticle-matrix interface. In this study, we investigate the role of oxygen in enhancing the mechanical properties of SiC nanoparticle-reinforced AMCs with the help of increased interfacial bonding. Aluminum powder incorporating oxygen was produced through the gas atomization, and thoroughly blended with 3 vol% SiC nanoparticles using the mechanical milling. The composite powder was consolidated by the hot-pressing process at 500 °C under an applied pressure of approximately 270 MPa. As a result, SiC nanoparticles were uniformly dispersed within an Al–O matrix, referred to as Al–O/SiC composites. An interfacial layer with a higher oxygen concentration than the matrix was observed between the SiC nanoparticles and the matrix. The interfacial layer partitioned by the oxygen exhibited an expanded aluminum lattice, which did not lead to oxide formation. Furthermore, oxygen influenced the bonding states of aluminum and carbon, promoting a robust interface through atomic oxygen bridging. Consequently, the Al–O/3vSiC composites exhibited higher values of Vickers hardness ∼18 % than the Al/3vSiC composites.